D Digitizing BUMDes: Application, Opportunities, and Challenges in the Special Region of Yogyakarta - Kevin Arya Pranajaya; Sakir sakir; Satria Iman Prasetyo (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
This study analyzes the challenges, opportunities, and application of BUMDes digitization in the Special Region of Yogyakarta. This research uses a qualitative descriptive research type research method, with a literature study using secondary data obtained by analysis of previous research and several mass media. The results of the study state that there are several challenges and opportunities in the digitization of BUMDes. In the digitalization challenges, there are; first, the ability of human resources to carry out or play a role in this activity is considered to have still not used digital platforms or is more inclined towards manuals, secondly adaptation of habits that require a person to adapt to any situation, thirdly production capacity where products produced by BUMDes must meet and comply with market needs and the last is the quality of production, where this is also the same as before that the products produced must meet quality standards so that they can compete in the global market. As for the opportunities for digitization in BUMDes, such as reaching unlimited buyers by accessing the market and selling for a total time.